Testimony and Intersubjectivity: A Process-Oriented Approach to Revelation - Bracken, Joseph A. (Philosophy & theology, 1987)
Following a brief examination of some remarks by Paul Ricoeur on the notion of testimony. I provide the outline or an analysis of revelation based upon certain key concepts of process philosophy. This is followed by a more specific interpretation within the context of Whitehead’s philosophy of process.